ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN USAHA KECIL MENENGAH: Studi Kasus Pada Usaha Kecil Dan Menengah Sentra Konveksi Di Klaten - Triyanto, Eko; Novitasari, Luky (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
This study aims to analyze some factors that influence the management of Small and Medium sized Enterprises (SMEs) in garment industries which are located in the Klaten Regency. The object of this research is small-Medium garment enterprises that are registered in the SME guidance by the Central Java Province Cooperative and SME Office in Klaten regency. Independent variables in this study are management accounting practices, contingent factors, and age of enterprises, whereas dependent variable in the study is the SMEs management. The data analysis technique uses multiple linear regression analysis. The results of data show that management accounting practices and contingent factors has influenceon SME management, significantly; while the age of enterprises variable does not have influence on the management of SME.